Respuesta :
Answer:
A. I only
Step-by-step explanation:
Given the functions
h(x)= -2x - 1 g(x)= -1/2x + 1/2
h(g(x) =h( -1/2x + 1/2)
=f((-x+1)/2)
We are to replace x in h(x) with -x+1/2
h((-x+1)/2) = -2(-x+1)/2 + 1
h((-x+1)/2) = -(-x+1)+1
h((-x+1)/2)= x-1+1
h((-x+1)/2) = x
h(g(x) = x
Also for g(h(x))
g(h(x)) = g(-2x-1)
Since g(x) = -x+1/2
g(-2x-1) = -(-2x-1)+1/2
g(-2x-1) =2x+1+1/2
g(-2x-1) = 2x+2/2
g(-2x-1) = 2(x+1)/2
g(-2x-1) = x+1
Sine g(h(x)) ≠ h(g(x)), hence both functions are not inverses of each other
Hence I. The function h(g(x)) = x is the only correct option. Option A is correct
The correct option is: A. I only
We have functions:
[tex]h(x)= -2x - 1 \\g(x)= -\frac{1}{2} x +\frac{1}{2} \\h(g(x)) =h(-\frac{1}{2} x +\frac{1}{2}) \\h(g(x))=f(\frac{-x+1}{2} )[/tex]
Now, replace x in h(x) by [tex]\frac{-x+1}{2}[/tex]
So,
[tex]h(\frac{-x+1}{2} ) = -2(\frac{-x+1}{2}) + 1\\h(\frac{-x+1}{2} ) = -(\frac{-x+1}{2}) + 1\\h(\frac{-x+1}{2} )= x-1+1\\h(\frac{-x+1}{2} )=x\\h(g(x)) = x[/tex]
Now, g(h(x))
g(h(x)) = g(-2x-1)
Since [tex]g(x) = \frac{-x+1}{2}[/tex]
[tex]g(-2x-1) = \frac{-(-2x-1)+1}{2} \\g(-2x-1) =\frac{2x+1+1}{2}\\g(-2x-1) =\frac{2x+2}{2}\\g(-2x-1) = x+1[/tex]
As g(h(x)) ≠ h(g(x)),
Therefore, both functions are not inverses of each other.
Hence A. I only
The function h(g(x)) = x is the only correct option.
So, option A is correct.
Learn more:https://brainly.com/question/10572318